Analisis Pengaruh Limbah Cair terhadap Kualitas Air Sungai di Kota Pekalongan - Elvinda Bendra Agustina; Yuni Lestiyanti; Yusril Ihza Tachriri; Nina Ulfiya (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
A study has been conducted on the effect of liquid waste on river water quality in Pekalongan city. Banger River, Meduri River, Loji River and Asem Binatur River in Pekalongan city are the objects studied. Water sampling was carried out at one polluted point. Based on water quality testing, it is known that among the four rivers tested, the rivers with the most polluted conditions are the Asem Binatur River, Loji River, Meduri River, and Banger River. This is because the samples were taken during the rainy season, so there is a possibility of soil erosion originating from areas along the river flow. The position of the Meduri River which is close to the sea is also a cause of the increase in the pollutant load in the test results, because the river is mixed with seawater when tidal flooding occurs. In addition, the Meduri River Basin (DAS) is a factory and industrial area, so that wastewater from these activities can also increase the pollutant load on the river. However, the majority of test results from the four rivers still exceed the required quality standards. This is due to the dense population, the large number of batik industries, and agricultural activities that produce waste and have an impact on the pollution of the surrounding rivers.